2014
DOI: 10.1186/1758-5996-6-84
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profile response to administration of epigallocatechin-3-gallate in high-fat-fed mice

Abstract: BackgroundObesity is associated with increased adipose tissue and glucose intolerance. High-fat diets (HFDs) are known to induce obesity and increase proinflammatory adipokines. The consumption of green tea may improve the health of obese individuals because it contains a potent antioxidant that has effects on body weight, energy expenditure and serum cholesterol concentrations.MethodsWe examined the effects of epigallocatechin-3-gallate (EGCG) (50 mg/kg body weight per day) or saline after 30 or 60 days of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 28 publications
2
19
0
1
Order By: Relevance
“…High‐fat diet‐fed rats treated with green tea extract or its extracted components (polyphenols, caffeine or polysaccharides) showed inhibition of weight gain which was caused by reduction in food utilisation, lowered serum triglyceride concentrations, inhibition of absorption of fatty acids and reduction of the expression of inflammatory genes . Similar results were obtained for EGCG treatment in high‐fat diet‐fed mice along with improvements in glucose tolerance . In high‐fat diet‐fed mice, 0.5% and 1% green tea extract dose‐dependently reduced body weight and 0.4% crude catechins also reduced body weight similar to 0.5% green tea.…”
Section: Green Tea: Catechinssupporting
confidence: 68%
“…High‐fat diet‐fed rats treated with green tea extract or its extracted components (polyphenols, caffeine or polysaccharides) showed inhibition of weight gain which was caused by reduction in food utilisation, lowered serum triglyceride concentrations, inhibition of absorption of fatty acids and reduction of the expression of inflammatory genes . Similar results were obtained for EGCG treatment in high‐fat diet‐fed mice along with improvements in glucose tolerance . In high‐fat diet‐fed mice, 0.5% and 1% green tea extract dose‐dependently reduced body weight and 0.4% crude catechins also reduced body weight similar to 0.5% green tea.…”
Section: Green Tea: Catechinssupporting
confidence: 68%
“…Just recently, evidence has been provided that cocoa power supplementation ameliorated the pro-inflammatory profile in high fat-fed obese mice ( 172 ). Same results have been obtained with the administration of epigallocatechin-3-gallate (EGCG) in high fat-fed mice ( 173 ). In obese women administration of green tea (EGCG) did not affect body weight, fat-mass, energy, homeostasis, cardiometabolic risk factor, and liver function ( 174 ).…”
Section: Polyphenolsmentioning
confidence: 60%
“…In previous studies showing the weight loss effect of EGCG, the administration period was several weeks. [23][24][25] The administration period in this study may be too short to observe body weight loss. A decrease in plasma octanoylated ghrelin reportedly reduces food intake 30) and body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that EGCG reduces food intake 22) and has an anti-obesity effect. 23,24) An elevation of thermogenesis and a decrease in lipid absorption are reportedly involved in the anti-obesity effect of EGCG. 25,26) However, the effect of EGCG on octanoylated ghrelin production has not yet been clarified.…”
mentioning
confidence: 99%